2014
DOI: 10.1093/nar/gku109
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of human and mouse Oct4 genes using engineered TALE and Cas9 transcription factors

Abstract: The newly developed transcription activator-like effector protein (TALE) and clustered regularly interspaced short palindromic repeats/Cas9 transcription factors (TF) offered a powerful and precise approach for modulating gene expression. In this article, we systematically investigated the potential of these new tools in activating the stringently silenced pluripotency gene Oct4 (Pou5f1) in mouse and human somatic cells. First, with a number of TALEs and sgRNAs targeting various regions in the mouse and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 61 publications
3
111
1
1
Order By: Relevance
“…Furthermore, since TAL is known as an active TAD in yeast 20 , we speculated that the dCas9-TV-mediated transcriptional activation may also work for mammalian cells, which are distantly related to Arabidopsis and rice cells. Indeed, when we targeted ASCL1 or OCT4 in human embryonic kidney (HEK) 293T cells with a single sgRNA 2,23 , we detected induction of endogenous ASCL1 by 46-fold and OCT4 by 14.6-fold, whereas dCas9-VP64 failed to enhance the expression of either gene (Fig. 2f).…”
mentioning
confidence: 96%
“…Furthermore, since TAL is known as an active TAD in yeast 20 , we speculated that the dCas9-TV-mediated transcriptional activation may also work for mammalian cells, which are distantly related to Arabidopsis and rice cells. Indeed, when we targeted ASCL1 or OCT4 in human embryonic kidney (HEK) 293T cells with a single sgRNA 2,23 , we detected induction of endogenous ASCL1 by 46-fold and OCT4 by 14.6-fold, whereas dCas9-VP64 failed to enhance the expression of either gene (Fig. 2f).…”
mentioning
confidence: 96%
“…Effector domains are fused to the carboxyl terminus of the dCas9 protein and can modulate gene expression from either strand of the targeted DNA sequence (Farzadfard et al 2013;Maeder et al 2013a;Perez-Pinera et al 2013). Genome-scale activation studies have indicated that the most robust levels of activation are generally observed when dCas9 activators are targeted to -400 to -50 bp upstream from the transcriptional start site (Gilbert et al 2014;Hu et al 2014). Additionally, dCas9 can inhibit gene expression by simply blocking transcriptional initiation or elongation through a process known as CRISPR interference (Qi et al 2013), although fusing dCas9 to transcriptional repressor domains can also lead to efficient silencing from the promoter Zalatan et al 2015).…”
Section: Targeted Transcription Factors Tools For Modulating Gene Expmentioning
confidence: 99%
“…For example, gene activation is stronger when dCas9 fusions to transactivators are co-expressed with multiple gRNAs targeting the same promoter [4650]. However, using multiple gRNAs may also increase the off-target binding activity of dCas9 yielding confounding results.…”
Section: Biochemical-specificitymentioning
confidence: 99%